1973
DOI: 10.1128/jvi.11.6.856-861.1973
|View full text |Cite
|
Sign up to set email alerts
|

Replication Process of the Parvovirus H-1 I. Kinetics in a Parasynchronous Cell System

Abstract: Parasynchronous cultures of hamster embryo cells were used to study some of the events in the replication process of the parvovirus H-1. Synthesis of viral DNA, viral hemagglutinating antigen, and infectious virus were examined. It was found that initiation of DNA synthesis, on which subsequent viral hemagglutinin synthesis was dependent, occurred at a specific time in late S-phase. Production of H-1 viral protein was shown to be sensitive to inhibition by aamanitin. The implications of these findings are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
52
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 25 publications
2
52
0
Order By: Relevance
“…The full spectrum of replicative events -from adsorption of the parental virus to intranuclear accumulation of progeny virions -takes 6-8 h in a fully susceptible, replication-competent cell [38,39]. As mentioned earlier, 'competence' for replication of autonomous parvoviruses or dependoviruses thereby appears to be conferred to the cells by quite different mechanisms.…”
Section: Helper Functions In the Replication Of Autonomous Paruouirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The full spectrum of replicative events -from adsorption of the parental virus to intranuclear accumulation of progeny virions -takes 6-8 h in a fully susceptible, replication-competent cell [38,39]. As mentioned earlier, 'competence' for replication of autonomous parvoviruses or dependoviruses thereby appears to be conferred to the cells by quite different mechanisms.…”
Section: Helper Functions In the Replication Of Autonomous Paruouirusesmentioning
confidence: 99%
“…In the case of autonomous parvoviruses, circumstantial observations in infected animals and experimental studies in cell cultures identified 'cycling' of cells, i.e., their active passage through the division cycle, as a major factor [38,40,41]. Using cell cultures in which the division cycles of individual cells had been synchronized by various treatments, the critical cellular function(s) then could be narrowed down to occur during duplication of the cellular genome (S-phase) [38,39,42]. Most investigators also agree that the critical function(s) become available in late S-phase.…”
Section: Helper Functions In the Replication Of Autonomous Paruouirusesmentioning
confidence: 99%
“…Minute virus of mice (MVM), a member of the helperindependent parvovirus group (12), contains a linear singlestranded DNA molecule of 5,081 nucleotides (3) that replicates in the S-phase nucleus of susceptible rodent cells grown in tissue culture (10,12,15,17). The termini of MVM single-stranded (SS) DNA are folded in a base-paired hairpin configuration (1,2,4,5) and play an essential role in viral DNA replication.…”
mentioning
confidence: 99%
“…The absence of rMVMpmediated transgene expression in these cells is therefore not surprising, on account of the well-known S-phase dependence of the parvoviral life cycle. [26][27][28][29] In the other, proliferating normal cells, the low level of transgene expression clearly indicates that rMVMp selectivity also depends on other cell properties, such as the differentiation state of the host cells (and especially, on whether they have undergone neoplastic transformation). This is precisely what makes such vectors interesting for tumor cell-targeted gene therapy.…”
mentioning
confidence: 99%